MACROFLORAL BIODIVERSITY CONSERVATION IN IFUGAO - Napoleon K. Taguiling (European Scientific Journal, ESJ, 2014)
Any biodiversity conservation effort starts from baseline information. A biodiversity study was then conducted in the province of Ifugao, Philippines to provide first hand information on the status of macrofloral biodiversity in the area. Rapid assessment using plot method was used in the inventory of macrofloral species. Ethnobotanical survey of key informants was also conducted to record knowledge of community members on the uses of plant species found in the locality. Results revealed 69 families 134 genera and 214 species of macroflora. Shannon’s diversity index for trees and shrubs showed 3.59 to 3.7 corresponding to relatively high diversity. Of the species recorded, 36 were endemic to the Philippines, 4 vulnerable based on the 2010 IUCN red list and under CITES Appendix II. Forest areas with lower elevation showed higher species diversity than those with higher elevation. Description of species importance values, dominance, similarity index and floristic checklist were provided. Ethnobotanical survey revealed 38 species used as food plants, 25 species used as medicinal plants, 26 species with socio-cultural importance, 2 species identified as source of strong fiber, 5 species with pesticidal properties, and 1 species utilized as organic fertilizer. Issues and problems related to macrofloral biodiversity and suggested solution actions were described. The forest areas in Ifugao are still rich in macrofloral diversity and can serve as a vital source for re-vegetation activities in areas with low plant density and diversity status. Leaving the remaining forest untouched and restoration of denuded forest cover in the other parts of Ifugao is vital in supporting macrofloral diversity conservation while mitigating climate change.